Unveiling the creatinine-to-albumin ratio: a novel predictor of acute heart failure post-TBI - Chen, Sheng; Hong, Xin; Cheng, Ailin; Wang, Jiayin; Jiang, Ling (Frontiers in Nutrition, 2026)
BackgroundThe creatinine-to-albumin ratio (CAR) has emerged as a potential biomarker for predicting acute heart failure (AHF) after traumatic brain injury (TBI) in various clinical settings. This study aimed to evaluate the association between CAR and AHF through logistic regression models and Receiver Operating Characteristic (ROC) analysis, both before and after propensity score matching (PSM), and to explore the dose–response relationship between CAR and AHF.MethodsA total of 1,899 patients were enrolled in the present study, including 1,836 TBI patients without AHF and 63 TBI patients with AHF. Logistic regression, ROC analysis, restricted cubic spline (RCS) modeling and CAR quartile-based trend tests were performed before and after PSM to assess the association between CAR and AHF. The unadjusted Model-1 and adjusted Model-2 (adjusted for gender, age, smoking, alcohol consumption, hypertension, and diabetes) were constructed prior to matching. One hundred twenty-four patients (62 patients in each group) were involved in the final analysis after PSM.ResultsBefore PSM, CAR was significantly associated with AHF after TBI in logistic regression (OR: 1.885, 95% CI: 1.534–2.318, p < 0.001), and demonstrated strong predictive performance in ROC analysis with an area under the curve (AUC) of 0.721 (p < 0.001). After PSM, CAR retained a significant association with AHF after TBI in logistic regression (OR: 1.597, 95% CI: 1.007–2.532, p = 0.047), although its ROC performance declined (AUC: 0.599, p = 0.050). RCS analysis revealed a nonlinear relationship, with higher CAR levels significantly increasing the odds of AHF (p < 0.001). Quartile-based trend analysis confirmed a positive association, with the highest CAR quartile (Q4) showing the greatest risk (OR: 5.980, p < 0.001 in Model-1; OR: 2.357, p = 0.062 in Model-2).ConclusionThe CAR is a significant and independent predictor of AHF following TBI, demonstrating a positive dose–response relationship with increasing CAR levels. These findings underscore the potential utility of CAR as a reliable biomarker for AHF following TBI.